Virtues and character development in Islamic ethics and positive psychology - Abdullah, Fatimah (Research Institute for Progression of Knowledge (RIPK), 2014)

(untitled)
Character building is one of the fundamental missions of the Prophet (pbuh) and should be incorporated in a holistic concept of progress and sustainable development of community within the worldview of Islam which unifies and balances the material with the spiritual dimension producing well being in this life and well being in after life. Islam emphasizes on the centrality of the role of morality in Islam, in both interpersonal and intra-personal relationship. To carry out moral and religious duties it requires the purification of the human soul through the application of the ethic of tawhid and the Prophetic teachings and learning. Self-purification or refinement of the human soul is not possible without proper observation and treatment and changing of human character or behavior. So much so to positively studying human emotions can be of help in Islamic ethical training; this is of value because the development of good character in Islam is mostly a process of dealing with one’s emotions. Even, the West is beginning to appreciate the role of spirituality or virtues in achieving mental and physical health and happiness. Psychology as a discipline that studies behavior and cognitive processes is most related to character building. After more than a century of pure non-godly secularism, psychology is now beginning to appreciate the role of spirituality and good character in the light of human development and progress. This is most apparent in the new areas of emotional intelligence, positive psychology and mindfulness as practiced in cognitive behavior therapy. Though they do not give such studies ethical terms, they are actually talking the same language of religious ethics. They are talking about virtues which are embedded in the value system such as mercy, empathy, patience, delaying of gratification, forgiveness, and acceptance and similar issues that Islamic or virtue ethics is propounding.